Researching and designing automated storage and retrieval system - Vương, Trí Dũng (Journal of Technical Education Science, 2013)
Warehouse is a important part of interprises. Warhouse managing, monitoring and controlling are a complex and difficult process. Therefore, Automated Storage and Retrieval System (ASRS) is a good solution for companies to save their resources in warehouse management. The main purpose of this thesis is reseaching automatic control programming, designing human-machine interface to manage and monitor, and constructing a suitable ASRS for small and medium vietnamese businesses.